APPLICATION OF ARTICLE 27 PARAGRAPH (1) OF LAW NUMBER 1 OF 2024 ON ELECTRONIC INFORMATION AND TRANSACTIONS AND COMPARATIVE STUDY WITH MALAYSIA AND TURKEY - Aji Malik; Yuliati; Bambang Sugiri (CV. RADJA PUBLIKA, 2025)
Article 27 paragraph (1) of Law Number 1 of 2024 concerning Electronic Information and Transactions remains a subject of debate due to the ambiguity in defining the term “decency,” which opens room for multiple interpretations and potentially hampers digital freedom of expression guaranteed under Article 28E paragraph (3) of the 1945 Constitution of the Republic of Indonesia. This normative tension becomes more evident through cases of digital expression that are classified as violations of decency, even when they take the form of satire or political criticism. This research aims to analyze the application of Article 27 paragraph (1) in Indonesian legal practice, assess its consistency with the principle of freedom of expression, and compare it with the regulation of decency norms in digital law in Malaysia and Turkey. The research employs a normative juridical method with statutory, conceptual, case, and comparative approaches, using primary data in the form of legislation and legal cases, as well as secondary data from literature and expert opinions. The findings show that the application of Article 27 paragraph (1) tends to be subjective, creates a chilling effect, and is disproportionate to the objective of protecting public morality. A comparison with Malaysia and Turkey demonstrates that decency norms can be formulated more clearly with strict limitations on obscene content without criminalizing political expression. These findings indicate the need for a reformulation of decency norms in the Electronic Information and Transactions Law to align with the principles of proportionality and the protection of digital freedom of expression.